Linking urban form to a liveable city - Noraziah Abdul Aziz; Abdul Samad Hadi (Environmental Management Society, Malaysia, 2007)
This paper intends to show the contribution and relationship of urban form to a liveable city, as many researchers pose the urban form as one of the factors that can worsen or improve the sustainability of the city. The paper will begin by exploring into the theoretical characteristics of the urban form at the macro and micro scale. Urban form models that match the Malaysian cities’ urban form are illustrated in this paper with the idea of giving a larger context of the living ecology for Malaysian communities. There are two types of cities, one that grows in an ad-hoc manner, and the other is being shaped by planners. This paper however, focuses only on a planned city that is the core city for Shah Alam. Consequently, this paper touches briefly on the liveable city concept which is currently being debated among the researchers as a more practical way of looking into the sustainable city issues. The liveable city framework for the city of Shah Alam is discussed and some preliminary findings are offered at the end of the paper